Effects of DIDS on the chick retinal pigment epithelium. I. Membrane potentials, apparent resistances, and mechanisms - Gallemore, RP (J Neurosci, 1989)
While little is known about the transport properties of the retinal pigment epithelium (RPE) basal membrane, mechanisms for anion movement across the basal membrane appear to be present (Miller and Steinberg, 1977; Hughes et al., 1984; Miller and Farber, 1984). This work examines the electrophysiological effects of the anion conductance blocker, 4,4′- diisothiocyanostilbene-2,2′-disulfonate (DIDS) on the basal membrane of an in vitro preparation of chick retina-RPE-choroid. DIDS (10–125 microM), added to the choroidal bath, decreased the transtissue potential by decreasing the potential across the RPE. Intracellular RPE recordings showed that DIDS affected the membrane potential in 2 phases, initially hyperpolarizing the basal membrane and then, after prolonged exposure, depolarizing the apical membrane. Resistance assessment by transtissue current pulses and intracellular c-wave recordings suggested that DIDS increased basal membrane resistance (Rba) during the first phase and increased apical membrane resistance (Rap) during the second phase. Measurements of intracellular Cl- activity (aiCl) showed that Cl- was actively accumulated by the chick RPE since it was distributed above equilibrium across both the apical and basal membranes. Perfusion of the basal membrane with 50 microM DIDS significantly increased aiCl-. The DIDS-induced basal membrane hyperpolarization, apparent increase in Rba, and increase in aiCl- are all consistent with Cl- -conductance blockade. During the second phase, apical membrane responsiveness to the light-evoked decrease in subretinal [K+]o (Oakley, 1977) was reduced an average of 58%. This finding, given the second-phase apical membrane depolarization and apparent increase in Rap, is consistent with a decrease in apical membrane K+ conductance.(ABSTRACT TRUNCATED AT 250 WORDS)